Study of Cold Rolling on the Transformation Mechanism, Microstructure, and Properties of 304 Austenitic Stainless Steel. Issue 4 (14th November 2021) - Li, Junchen; Pei, Weiyang; Zhao, Mengyu; Zhao, Dejiang; Shi, Xulin
Abstract : The work hardening mechanism and microstructure properties of 304 austenitic stainless steel (304 ASS) during cold rolling are studied by means of electron backscatter diffraction (EBSD), a transmission electron microscope (TEM), X‐ray diffraction (XRD), hardness test, and permeability measurement. Meanwhile, the mechanical properties and permeability properties of 304 ASS with different cold rolling reductions are investigated. The results show that when the cold rolling reduction is in the range of 5−20%, there are two kinds of phase transformations (γ → ϵ → α′ and γ → α′) in the 304 ASS. With increase in cold rolling reduction (cold rolling reduction ≥ 23%), γ → α′ became the main phase transformation. It is known that α′‐martensite significantly affects the permeability of 304 ASS. To obtain the weak magnetic property that meets the needs of end users, the cold rolling reduction should be controlled at 5−10%. Abstract : Different cold rolling reductions lead to different martensitic transformation progresses and work hardening mechanisms of 304 austenitic stainless steel (ASS). These result in the diverse property variation law of 304 ASS. The cold rolling reduction should be controlled at 5−10% to meet the needs of weak permeability and sufficient hardness and strength.